2019
DOI: 10.1097/md.0000000000016601
|View full text |Cite
|
Sign up to set email alerts
|

Fermented milk containing Lactobacillus paracasei and Glycyrrhiza glabra has a beneficial effect in patients with Helicobacter pylori infection

Abstract: Background:Lactobacillus paracasei and Glycyrrhiza glabra have been reported as having beneficial effects on Helicobacter pylori infection. We aimed to assess the efficacy and safety of fermented milk containing L paracasei HP7 and G glabra in patients with H pylori infection.Methods:This multicenter, prospective, randomized, double-blind, placebo-controlled clinical trial was conducted in 2 hospitals from April to December 2017. Patients with H pylori infection were randomized into either the treatment group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 69 publications
(83 reference statements)
0
27
0
Order By: Relevance
“…Recent studies have shown that the Lactobacillus paracasei ( L. paracasei ) treatment can alleviate inflammation-related disorders by modulating the production of anti- and pro-inflammatory cytokines ( 9 , 10 ). Furthermore, clinical studies also revealed the important role of L. paracasei supplementation in ameliorating inflammation in humans ( 11 , 12 ). Mechanically, L. paracasei can act as a probiotic to improve gut microbial composition ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the Lactobacillus paracasei ( L. paracasei ) treatment can alleviate inflammation-related disorders by modulating the production of anti- and pro-inflammatory cytokines ( 9 , 10 ). Furthermore, clinical studies also revealed the important role of L. paracasei supplementation in ameliorating inflammation in humans ( 11 , 12 ). Mechanically, L. paracasei can act as a probiotic to improve gut microbial composition ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional foods containing probiotics have been demonstrating effectiveness to prevent or treat health problems, including digestive disorders, such as irritable bowel syndrome and necrotizing enterocolitis [ 1 , 2 , 3 ]. In particular, those formulations containing lactobacilli are recognized for their ability to modulate the human microbiota and induce anti-inflammatory and anti-oxidant effects [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are commonly found in dairy foods, such as milks, yogurts and cheeses [ 4 , 7 , 8 ]; however, fruit juices may also be excellent vehicles for development of probiotic products due to their nutritional properties and presence of bioactive compounds (vitamins, phenolic acids, flavonoids and other anti-oxidant compounds) [ 9 , 10 , 11 ]. The use of fruit juices containing probiotics also gives opportunities to individuals with specific conditions (lactose intolerance, allergy to milk components and vegetarians) to benefit from the consumption of these bacteria [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, antibiotic therapy promotes an imbalance in the intestinal microbiota and increased levels of resistant bacteria [110], as well as species associated with persistent gastric inflammation and gastric carcinogenesis [111]. This situation justifies probiotic supplementation, aiming to reduce undesirable changes in the intestinal microbiota, promote the eradication of H. pylori [108,112], produce significant improvements in gastrointestinal symptoms, and, consequently, in the quality of life of individuals [108,109]. The combination of probiotics with antibiotic therapy for the eradication of H. pylori was suggested in the Thailand Consensus, held in 2015 [110].…”
Section: Prevention and Treatment Of Infection With Probioticsmentioning
confidence: 99%